Unveiling the Gut Microbiota of Pig-Tailed Macaque (Macaca nemestrina) in Selected Habitats in Malaysia - Nur Azimah, Osman; Millawati, Gani; Roberta Chaya Tawie, Tingga; Muhammad Abu Bakar, Abdul Latiff; Mohd Ridwan, Abd Rahman; Eddie, Chan; Badrul Munir, Md Zain (John Wiley & Sons Ltd., 2024)
The gut microbiota plays an important role in primates, which may be associated with their habitat. In Malaysia, pig-tailed macaques (Macaca nemestrina) live in different habitat environments and have traditionally been used for coconut plucking for more than a century. There is currently no information regarding the gut microbiota of this macaque in Malaysia. To address this oversight, this study employed a fecal metabarcoding approach to determine the gut microbiota composition of pig-tailed macaques and establish how these microbial communities correspond with the macaque external environments of residential area, forest edge, and fragmented forest.To determine this connection, 300 paired-end sequences of 16S rRNA were amplified and sequenced using the MiSeq platform. In the pig-tailed macaque fecal samples, we identified 17 phyla, 40 orders, 52 families, 101 genera, and 139 species of bacteria. The most prevalent bacterial families in the gut of pig-tailed macaques were Firmicutes (6.31%) and Proteobacteria (0.69%). Our analysis did not identify a significant difference between the type of environmental habitat and the gut microbiota composition of these macaques. There was great variation in the population richness and bacterial community structure. The abundance of Firmicutes and Proteobacteria helps this macaque digest food more easily while maintaining a healthy gut microbiota diversity. Exploring the gut microbiota provides an initial effort to support pig-tailed macaque conservation in the future.